2019
DOI: 10.1016/j.cegh.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception and knowledge of hepatitis B infection among cleaners in a tertiary hospital in Nigeria: A cross-sectional study

Abstract: Background: Hepatitis B infection is a leading pathogenic infection that constitutes occupational hazard to health care workers. The current study examines the knowledge of hepatitis B infection and hepatitis B vaccination and uptake of the vaccine among the cleaners in a tertiary hospital in Nigeria. Materials and methods: A cross-sectional hospital-based study of 89 cleaners using a standardized interviewer-administered questionnaire for data collection was conducted. Data were analyzed with SPSS version 21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 15 publications
2
17
1
Order By: Relevance
“…While the HBV vaccine can effectively prevent the spread of HBV among adults, migrant workers’ lower vaccination prevalence than permanent workers is due to their poorer cognition of HBV and the HBV vaccine, lower education level and poorer health awareness levels, living in groups and lower accessibility to health care services [ 8 11 ]. While previous Chinese studies have identified an individual’s knowledge and cognition of HBV and the HBV vaccine as key factors explaining HBV vaccination intentions and behavior, these studies only employed partial measures of HBV cognition [ 12 14 ]. One exception was a study using protection motivation theory (PMT) to specify and test a cognition model of migrant workers’ HBV vaccination intention, but the migrant-industry characteristics and key PMT factors, such as response costs, were excluded from the model [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the HBV vaccine can effectively prevent the spread of HBV among adults, migrant workers’ lower vaccination prevalence than permanent workers is due to their poorer cognition of HBV and the HBV vaccine, lower education level and poorer health awareness levels, living in groups and lower accessibility to health care services [ 8 11 ]. While previous Chinese studies have identified an individual’s knowledge and cognition of HBV and the HBV vaccine as key factors explaining HBV vaccination intentions and behavior, these studies only employed partial measures of HBV cognition [ 12 14 ]. One exception was a study using protection motivation theory (PMT) to specify and test a cognition model of migrant workers’ HBV vaccination intention, but the migrant-industry characteristics and key PMT factors, such as response costs, were excluded from the model [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of HEV is very low compared with the others, especially hepatitis B virus (HBV). Numerous articles that investigated different aspects of HBV infections in Nigeria [12], [13], [14] and few papers are available for HEV infection.…”
Section: Introductionmentioning
confidence: 99%
“…While the HBV vaccine can effectively prevent the spread of HBV among adults, migrant workers' lower vaccination prevalence than permanent workers is due to their poorer cognition of HBV and the HBV vaccine, lower education level and poorer health awareness levels, living in groups and lower accessibility to health care services [8][9][10][11]. While previous Chinese studies have identi ed an individual's knowledge and cognition of HBV and the HBV vaccine as key factors explaining HBV vaccination intentions and behavior, these studies only employed partial measures of HBV cognition [12][13][14]. One exception was a study using protection motivation theory (PMT) to specify and test a cognition model of migrant workers' HBV vaccination intention, but the migrant-industry characteristics and key PMT factors, such as response costs, were excluded from the model [15].…”
Section: Introductionmentioning
confidence: 99%